Renewing polyethylene: insertion copolymerization of sugar derived hydrophilic monomers with ethylene - Rajput, Bhausaheb S.; Pawal, Sandip B.; Bodkhe, V. Dnyaneshwar; Rao, I. Nagamalleswara; Sainath, Annadanam V. Sesha; Chikkali, Samir H. (European Polymer Journal, 2020)
Although highly desirable, insertion copolymerization of renewable resource derived functional olefins with ethylene has been rarely investigated. Herein, we report insertion copolymerization of challenging sugar derived isohexide mono-enes with ethylene in the presence of Pd-phosphinesulfonate acetonitrile catalyst (C1). Thus, copolymerization of ethylene with isomannide mono-ene (2a), isosorbide mono-ene (2b'), isoidide mono-ene (2c) and methacryl-2,3,4,6-tetra-O-acetyl-D glucopyranoside (2d) afforded corresponding functionalized polyethylene (P2a-1 to P2d-1). High temperature proton NMR investigations revealed enchainment of 2a-2c in polyethylene backbone and the highest incorporation of 1.45% was observed for 2c. The high temperature proton NMR results were further corroborated by solid state C-13 NMR and IR spectroscopy. Gel permeation chromatography analysis displayed weight average molecular weight in the range of 13.0-27.2 x 10(3) g/mol. The thus prepared copolymers revealed melting temperature in the range of 117-126 degrees C. Relatively reduced melting temperature compared to neat polyethylene may suggest an irregular arrangement of pendant functional group on polyethylene main chain.
Keywords: Hydrophilic polyethylene; insertion copolymerization; Isohexide mono-enes; Polyethylene; Sugar

Designing of imine thiophene-ligated metal-complexes and implication in ethylene polymerization - Shaikh, Maulali H.; Ramekar, V. Rohan; Jawoor, Shailaja; Dash, Soumya R.; Birajadar, Rajkumar S.; Pawal, Sandip B.; Thenmani, Nandakumar; Vanka, Kumar; Chikkali, Samir H. (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2024)
Polyethylene is the single largest volume polymer produced globally using Ziegler-type catalysts. Numerous modifications have been reported in search of a better catalyst that can control molecular weight, polydispersity, and branching. In our attempts to identify a suitable imine thiophene-ligated chromium complex, we examined 9 different titanium complexes computationally. The DFT investigations considered barriers for insertion, propagation, and termination by beta-H elimination or chain transfer, and identified N-(4-methoxyphenyl)-2-phenyl-1-(thiophen-2-yl)ethan-1-imine(L9) as the most suitable ligand. Subsequently, L9 was prepared in good yield (70%) by condensing 2-phenyl-1-(thiophen-2-yl)ethan-1-one with 4-methoxyaniline. Ligand L9 was treated with early transition metal precursors (Ti, Cr, Zr) to generate a homogenous catalyst. The identity of these catalysts was unambiguously ascertained using a combination of NMR, ICP, FT-IR, UV-Vis spectroscopy, and ESI-MS. The performance of L9-ligated titanium complex [Cat.1] was examined in ethylene polymerization using MMAO as a co-catalyst. Insertion of ethylene was tracked using high-pressure NMR experiments and Cat.1 was found to be active in the polymerization. Ethylene polymerization conditions were optimized to obtain high activity and molecular weight polyethylene. The chromium complex [Cat.2] outperformed the Ti and Zr-derived catalysts with the highest TOF of 6294 mol of PE/mol of Cr/h. Cat.2 produced high molecular weight, high-density polyethylene.
Keywords: Cr-complexes; DFT; high-density polyethylene; Imine thiophene ligand; Polyethylene